Pengaruh Partisipasi Anggaran, Asimetri Informasi, Ketidakpastian Lingkungan, Budaya Organisasi, dan Komitmen Organisasi pada Senjangan Anggaran - Wimba Wardhana, Anak Agung Gde; Gayatri, Gayatri (E-Jurnal Akuntansi, 2018)
Budgetary slack is a budgeting process that found intentional distortion by lowering budgeted revenues and increasing budgeted costs. This study aims to determine the effect of budgetary participation, information asymmetry, environmental uncertainty, organizational culture and organizational commitment on budget slack at State General Hospital Jembrana District. This research was conducted on the authorized personnel in budget preparation at RSU Negara as many as 40 people. The result of hypothesis testing shows that budget participation variable has positive effect on budget slack, information asymmetry has positive effect on budget slack, environmental uncertainty has positive effect on budget slack, organizational culture has negative effect on budget slack, and organizational commitment has negative effect on budget slack. Keywords: budgetary participation, information asymmetry, environmental uncertainty, organizational culture, organizational commitment, budgetary slack